Internalization of G-protein-coupled receptors: Implication in receptor function, physiology and diseases. Issue 2 (April 2018) - Calebiro, Davide; Godbole, Amod
Abstract : G protein-coupled receptors (GPCRs) are the largest family of membrane receptors and mediate the effects of numerous hormones and neurotransmitters. The nearly 1000 GPCRs encoded by the human genome regulate virtually all physiological functions and are implicated in the pathogenesis of prevalent human diseases such as thyroid disorders, hypertension or Parkinson's disease. As a result, 30–50% of all currently prescribed drugs are targeting these receptors. Once activated, GPCRs induce signals at the cell surface. This is often followed by internalization, a process that results in the transfer of receptors from the plasma membrane to membranes of the endosomal compartment. Internalization was initially thought to be mainly implicated in signal desensitization, a mechanism of adaptation to prolonged receptor stimulation. However, several unexpected functions have subsequently emerged. Most notably, accumulating evidence indicates that internalization can induce prolonged receptor signaling on intracellular membranes, which is apparently required for at least some biological effects of hormones like TSH, LH and adrenaline. These findings reveal an even stronger connection between receptor internalization and signaling than previously thought. Whereas new studies are just beginning to reveal an important physiological role for GPCR signaling after internalization and ways to exploit it for therapeutic purposes, future investigations will be required to explore its involvement in human disease.